Human resource planning and development of pharmaceutical sector in Malaysia related to Malaysian National Medicines Policy: a pilot study - Shamsudin, Siti Hadijah; Sulaiman, Shamsul Akmar (2010)
The objective of this study is to investigate the internal consistency of the scale and the test reliability of the questionnaire to create a better understanding on the expectations of pharmaceutical companies and educational institutions with Malaysian government in planning human resource development in the pharmaceutical sector. The study was carried out in one week interval by experts in the field. 28 out of 30 self administered questionnaire were completed (96.7%-responds rates). Cronbach's x coefficients computed to measure the internal consistency and reliability of all questions gave values of more than 0.7(0.746, 0.774, 0.894), which show the questionnaires are reliable. The questionnaire provides a reliable, valid and easy-to-administer tool for assessing personal perspective on the human resource planning and development of pharmaceutical sector in Malaysia. The analysis of the survey results showed gaps between what the government agencies are doing and what the industrial pharmacists and academicians expert from them with regard to developing s successful knowledge-based economy. In summary, the research team hopes that the findings of this study will create a better understanding of the expectations of industrial pharmacists and academicians from government agencies to lead to the knowledge-based economy.